Innovative Mobile Application for Self-Directed Learning in Massage Therapy: Development and Usability Study - Supriatin, Supriatin; Dioso, Regidor III; Hassan, Datin Dr. Hafizah Che (Qualitative and Quantitative Research Center, 2025)
Mobile health education applications for parents are emerging as powerful tools to support self-directed learning and improve skills such as infant massage for better child health outcomes. The usability and availability of a smartphone app in Indonesia for improving body weight among children with low birth weights are being under-investigated due to the growing interest in self-directed learning of mobile application tools. This research aimed to document a mobile application's development and usability testing stages on self-directed learning of massage therapy. The methodology, developed using a server–client architecture with the HyperText Transfer Protocol and Web API, was evaluated during the prototype phase using the Think-Aloud method and the Smartphone Usability Questionnaire. The result showed that the agreement of the content reported 95%, indicating good validity. Thirteen out of the fifteen participants used the notification page to limit their time on social media. The mean IMI score was 4.34 (SD=0.45) out of 7. The App had a SUS score of 68.16 (SD = 9.34). The participants gave the app an average of 18.45 (SD = 1.76). The test revealed that the app prototype was designed with the end user in mind, ensuring high usability. The app provides health education and serves as a foundation for future mobile applications for parents to prevent low-birth weight.